Commentary on Financial Privacy - Lynn M. LoPucki (Washington University Law Quarterly, 1999)
My three criticisms are this: First, Peter frames the problem as privacy versus government surveillance, thus ignoring the best solution to the problem, which is to make more information public. Second, Peter exaggerates the human need for privacy by presenting the need as immutable and essentially coextensive with embarrassment. People do not need nearly the privacy they think they do. Third, if Peter’s broad view of privacy holds, then you can forget about the information age.
Keywords: Right of privacy; Financial services industry; Electronic surveillance; Phase 2 Plus (Company); Bank secrecy